Regulation of Calvarial Osteogenesis by Concomitant De-repression of GLI3 and Activation of IHH Targets - Veistinen, Lotta K.; Mustonen, Tuija; Hasan, Md. Rakibul; Takatalo, Maarit; Kobayashi, Yukiho; Kesper, Dörthe A.; Vortkamp, Andrea; Rice, David P. (Frontiers in Physiology, 2017)
Loss-of-function mutations in GLI3 and IHH cause craniosynostosis and reduced osteogenesis respectively. In this study, we show that Ihh ligand, the receptor Ptch1 and Gli transcription factors are differentially expressed embryonic mouse calvaria osteogenic condensations. We show that in both Ihh-/- and Gli3Xt-J/Xt-J embryonic mice, the normal gene expression architecture is lost and this results in disorganized calvarial bone development. RUNX2 is a master regulatory transcription factor controlling osteogenesis. In the absence of Gli3, RUNX2 isoform II and IHH are upregulated, and RUNX2 isoform I downregulated. This is consistent with the expanded and aberrant osteogenesis observed in Gli3Xt-J/Xt-J mice, and consistent with Runx2-I expression by relatively immature osteoprogenitors. Ihh-/- mice exhibited small calvarial bones and HH target genes, Ptch1 and Gli1, were absent. This indicates that IHH is the functional HH ligand, and that it is not compensated by another HH ligand. To decipher the roles and potential interaction of Gli3 and Ihh, we generated Ihh-/-;Gli3Xt-J/Xt-J compound mutant mice. Even in the absence of Ihh, Gli3 deletion was sufficient to induce aberrant precocious ossification across the developing suture, indicating that the craniosynostosis phenotype of Gli3Xt-J/Xt-J mice is not dependent on IHH ligand. Also, we found that Ihh was not required for Runx2 expression as the expression of RUNX2 target genes was unaffected by deletion of Ihh. To test whether RUNX2 has a role upstream of IHH, we performed RUNX2 siRNA knock down experiments in WT calvarial osteoblasts and explants and found that Ihh expression is suppressed. Our results show that IHH is the functional HH ligand in the embryonic mouse calvaria osteogenic condensations, where it regulates the progression of osteoblastic differentiation. As GLI3 represses the expression of Runx2-II and Ihh, and elevates Runx2-I and IHH may be regulated by RUNX2, these results raise the possibility of a regulatory feedback circuit to control calvarial osteogenesis and suture patency. Taken together, RUNX2-controlled osteoblastic cell fate is regulated by IHH through concomitant inhibition of GLI3-repressor formation and activation of downstream targets.